Serum ischemia modified albumin and dynamic thiol/disulfide homeostasis in early- and late-onset preeclampsia - Adanas Aydin, Gultekin; Ozgen, Gulten; Neselioglu, Salim; Erel, Ozcan (Annals of Medical Research, 2021)
Aim: In the present study, we aimed to evaluate serum IMA, IMA/albumin ratio, and DTDH levels in patients with early- and late-onset PE compared to healthy controls.Impaired homeostasis between oxidant and antioxidant mechanisms, inflammatory processes, and endothelial dysfunction play a key role in the pathogenesis of preeclampsia (PE). Serum ischemia modified albumin (IMA) and dynamic thiol/disulfide homeostasis (DTDH) levels are elevated in the presence of inflammation, oxidative stress, and endothelial dysfunction. Material and Methods: A total of 24 patients with early-onset PE and 62 patients with late-onset PE were included.The control group consisted of 46 healthy controls with similar gestational weeks. Serum samples were collected and IMA, albumin, and native, total, and disulfide thiol levels analyzed. Corrected IMA/albumin ratios were also calculated.Results: Disulfide levels, disulfide/native and disulfide/total thiol levels were higher in patients with early-onset PE compared to late-onset patients(p=0.008, p=0.022, and p=0.021, respectively). However, there was no significant difference between the late-onset PE patients and late-onset PE controls. Although there was no significant difference in the IMA levels between the patient and control groups, the IMA/albumin ratio was higher in the early-onset and late-onset PE patients, compared to the control group. However, there was no significant difference between the early-onset and late-onset PE patients.Conclusion: Our study results showed increased disulfide levels, disulfide/native thiol, disulfide/total thiol and IMA/albumin ratio in the early-onset PE patients, indicating increased oxidative stress in the pathogenesis of PE. In the late-onset PE patients, there was an increase only in the IMA/albumin ratio. However, further large-scale, prospective studies are needed to confirm the diagnostic value of these markers in the clinical practice.